Work-related burnout among public secondary school teachers is significantly influenced by the psychosocial work factors: a cross-sectional study from Ethiopia - Belay, Azanaw Asega; Gasheya, Kassahun Ayele; Engdaw, Garedew Tadege; Kabito, Gebisa Guyasa; Tesfaye, Amensisa Hailu (Frontiers in Psychology, 2023)
Introduction: Work-related burnout (WRB) is the degree of physical and psychological fatigue and exhaustion perceived by individuals as related to their work. Even though the condition is widespread across various occupations, teachers inevitably experience high levels of burnout in their work, which can have long-term effects on their health and well-being. However, in developing countries such as Ethiopia, the lack of reliable data on psychosocial hazards, including work-related burnout, often encumbers officials from planning preventive measures. This study investigated the prevalence and contributing factors of work-related burnout among public secondary school teachers in Gondar City, northwestern Ethiopia. Methods: An institution-based cross-sectional study was conducted from May to June 2022. A sample of 588 teachers was recruited using simple random sampling. Work-related burnout was assessed using a standardized seven-item Copenhagen Burnout Inventory (CBI). The data were collected through a self-administered questionnaire. The collected data were entered into EpiData and analyzed using SPSS. A multivariable logistic regression analysis was used to identify factors associated with work-related burnout. Results: The overall response rate was 94.05% (N=553). The majority of participants, 356 (64.4%), were male. The mean (±SD) age of the participants was 38.74 (±7.65) years. This study demonstrated that the prevalence of work-related burnout among school teachers in the past 12 months was 37.4% (n=207). High job demands, job stress, job dissatisfaction, low role clarity, and student demotivation were found to be the psychosocial work factors that significantly influenced the prevalence of work-related burnout among school teachers. Conclusion: This study highlights the high prevalence of work-related burnout among public secondary school teachers. Psychosocial work factors such as job demands, job stress, job satisfaction, role clarity, and student demotivation were significant factors influencing work-related burnout. To reduce the condition, it is recommended to take measures to cope with high job demands, improve stress management skills, promote job satisfaction strategies, clarify teachers' responsibilities, and use effective teaching practices to motivate students. In general, addressing psychosocial work factors needs to be central to efforts to prevent teacher burnout.